Teaching Standards Framework project : final report. - Sachs, Judyth (Australian Learning and Teaching Council, 2011)
This is a report from The Teaching Standards Framework (TSF) project, that was initiated to facilitate the development of teaching standards for the Australian higher education sector. Macquarie University had developed teaching standards frameworks at both the institutional and individual level for its own internal auditing purposes in 2009. The role of the standards frameworks was to provide criteria that could be used to assess institutional and individual performance data in a way that contributed to the continual improvement of learning and teaching. In early 2010, Macquarie proposed that the frameworks be tested as a possible tool for assessing teaching quality across the Australian university sector. All Australian universities were invited to participate, 17 submitted an expression of interest with nine universities involved in testing and re-designing the framework between August and December 2010, two at their own expense. The testing of the framework has resulted in six standards that provide institutions with a way of benchmarking the quality of their teaching, learning environment and curriculum. [Executive summary, ed]